Development and validation of the Diagnostic Interview Adjustment Disorder (DIAD). Issue 2 (30th January 2014) - Cornelius, L. R.; Brouwer, S.; de Boer, M. R.; Groothoff, J. W.; van der Klink, J. J. L.
Abstract Adjustment disorders (ADs) are under‐researched due to the absence of a reliable and valid diagnostic tool. This paper describes the development and content/construct validation of a fully structured interview for the diagnosis of AD, the Diagnostic Interview Adjustment Disorder (DIAD). We developed the DIAD by partly adjusting and operationalizing DSM‐IV criteria. Eleven experts were consulted on the content of the DIAD. In addition, the DIAD was administered by trained lay interviewers to a representative sample of disability claimants (n = 323). To assess construct validity of the DIAD, we explored the associations between the AD classification by the DIAD and summary scores of the Kessler Psychological Distress 10‐item Scale (K10) and the World Health Organization Disability Assessment Schedule (WHODAS) by linear regression. Expert agreement on content of the DIAD was moderate to good. The prevalence of AD using the DIAD with revised criteria for the diagnosis AD was 7.4%. The associations of AD by the DIAD with average sum scores on the K10 and the WHODAS supported construct validity of the DIAD. The results provide a first indication that the DIAD is a valid instrument to diagnose AD. Further studies on reliability and on other aspects of validity are needed. Copyright © 2014 John Wiley & Sons, Ltd.